2013
DOI: 10.1530/erc-12-0344
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin receptor EP3 mediates growth inhibitory effect of aspirin through androgen receptor and contributes to castration resistance in prostate cancer cells

Abstract: Although numerous epidemiological studies show aspirin to reduce risk of prostate cancer, the mechanism of this effect is unclear. Here, we first confirmed that aspirin downregulated androgen receptor (AR) and prostate-specific antigen in prostate cancer cells. We also found that aspirin upregulated prostaglandin receptor subtype EP3 but not EP2 or EP4. The EP3 antagonist L798106 and EP3 knockdown increased AR expression and cell proliferation, whereas the EP3 agonist sulprostone decreased them, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…We previously revealed that aspirin, a classic NSAID, reduced EP2 and induced EP3 expression in prostate cancer cell lines, and that EP3 signaling has an important role in the antitumor effect of aspirin. 37 Since celecoxib similarly reduced EP2 and induced EP3 expression, EP3 signaling may also participate in the antitumor activity of celecoxib in some contexts.…”
Section: Discussionmentioning
confidence: 99%
“…We previously revealed that aspirin, a classic NSAID, reduced EP2 and induced EP3 expression in prostate cancer cell lines, and that EP3 signaling has an important role in the antitumor effect of aspirin. 37 Since celecoxib similarly reduced EP2 and induced EP3 expression, EP3 signaling may also participate in the antitumor activity of celecoxib in some contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Selective EP1 and EP3 agonist 19(R)-hydroxy PGE1 could restore drug resistance of HepG2/ADM, while selective EP2 agonist CAY10399 and selective EP4 agonist L-902,688 had similar effect on U87MG. PGE2 is the key in COX-2 regulating the express of multidrug resistance proteins in cancer cells (Woodward et al, 1993;Tani et al, 2001;Takaoka et al, 2008;Henderson et al, 2011;Hu et al, 2013;Kashiwagi et al, 2013). COX-2/PGE2 pathway could enhance the cancer cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation arising from a variety of physiological insults is thought to be a major cause and promoter of various cancers, including prostate cancer [3740]. Inflammation of the prostate is associated with the induction of cytokines, chemokines, and growth factors, as well as COX-2, which is also overexpressed in prostate cancer [21, 41].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Inflammation of the prostate is associated with the induction of cytokines, chemokines, and growth factors, as well as COX-2, which is also overexpressed in prostate cancer [21, 41]. Given their anti-inflammatory roles in the reduction of COX activity and prostaglandin synthesis, therefore [37, 42], it has been speculated that treatment with NSAIDs might reduce the risk of prostate cancer [43]. …”
Section: Prostate Cancermentioning
confidence: 99%